Causes of Mortality in Rheumatoid Arthritis - Zafer Günendi,; Aslı Gençay Can, (Archives of Rheumatology, 2008)
Patients with rheumatoid arthritis have a shorter total life expectancy than the general population of the same age and sex. Generally, mortality due to rheumatoid arthritis occurs 8-10 years after the disease onset. Mortality risk decreases with use of disease modifying antirheumatic drugs. The most common causes of mortality in rheumatoid arthritis are cardiovascular system diseases and infections. Patients with rheumatoid arthritis have a two-fold increase in cardiovascular mortality. Atherosclerosis which is triggered by systemic inflammation is an important factor in the development of cardiovascular disease. The other causes of mortality in rheumatoid arthritis are pulmonary system diseases, renal diseases, drug side effects, amyloidosis, malignancy, vasculitis, crycoarytenoid arthritis, catastrophic antiphospholipid syndrome, Felty's syndrome and atlantoaxial subluxation. (Rheumatism 2008 23: 91-6)